PENGARUH RAWAT LUKA GANGRENE TERHADAP PENCEGAHAN TINDAKAN AMPUTASI DAN PENURUNAN TINGKAT KECEMASAN - lenni saragih; Muhammad Faruq Afifuddin; Imam Subekti; Rossyana Septyasih (Jurnal Keperawatan Terapan, 2020)
Foot ulcer or gangrene is one of the complications of diabetes mellitus disease. with gangrene will be more at risk of amputation 10 until 30 times than in the general population and can be prevented if the condition of the wound occurs by wound care and debridement in addition to taking medication and diet as recommended. Patients with gangrene ulcers have anxiety, especially anxiety about amputation, anxiety has a strong influence on blood glucose levels in patients. The focus of this study is the effect of gangrene wound care on the prevention of amputation and decreased anxiety in type 2 diabetes mellitus patients. This research method uses descriptive case studies with 1 subject. Data collection using questionnaire interview techniques and observation for 2 weeks. The results of this study found that anxiety at the first meeting found moderate anxiety with a score of 26, with blood sugar 360 mg per dl and wounds with a degree of 4 and at the last meeting the data obtained that subjects received a mild degree of anxiety with a score of 8 and with a degree of wagner wound. In conclusion, treating wounds routinely and appropriately can reduce anxiety levels which have an impact on the decline in blood sugar levels, and a reduction in the degree of injury.